Gypenoside Protects Cardiomyocytes against Ischemia-Reperfusion Injury via the Inhibition of Mitogen-Activated Protein Kinase Mediated Nuclear Factor Kappa B Pathway In Vitro and In Vivo - Yu, Haijie; Shi, Liye; Qi, Guoxian; Zhao, Shijie; Gao, Yuan; Li, Yuzhe (Frontiers in Pharmacology, 2016)
Gypenoside (GP) is the major effective component of Gynostemma pentaphyllum and has been shown to encompass a variety of pharmacological activities. In this study, we investigated whether GP is able to protect cardiomyocytes against injury myocardial ischemia-reperfusion (I/R) injury by using in vitro oxygen-glucose deprivation-reoxygenation (OGD/R) H9c2 cell model and in vivo myocardial I/R rat model. We found that GP pre-treatment alleviated the impairments on the cardiac structure and function in I/R injured rats. Moreover, pre-treatment with GP significantly inhibited IкB-α phosphorylation and nuclear factor (NF)-кB p65 subunit translocation into nuclei. GP and the MAPK pathway inhibitors also reduced the phosphorylation of ERK, JNK, and p38 in vitro. Specific inhibition of ERK, JNK, and p38 increased the cell viability of OGD/R injured cells. Taken together, our data demonstrated that GP protects cardiomyocytes against I/R injury by inhibiting NF-кB p65 activation via the MAPK signaling pathway both in vitro and in vivo. These findings suggest that GP may be a promising agent for the prevention or treatment of myocardial I/R injury.